Paratesticular Dedifferentiated Liposarcoma with Rhabdomyoblastic Differentiation: A Case Report and Review of the Literature - Keles, Ahmet; Arikan, Ozgur; Keser, Ferhat; Yildirim, Ayse Nur Toksoz; Yildirim, Asif (Prague medical report, 2023)
Liposarcomas of the paratesticular tissue is a rare pathological entity. The symptoms are similar to inguinal hernias or hydroceles. We present the case of an 84-year-old man with a rare paratesticular liposarcoma that manifested as painless right hemiscrotal swelling. Testicular tumour markers were negative. Imaging revealed a heterogeneous mass with a fat component. He underwent a radical orchiectomy on the left side to remove the associated mass. This revealed dedifferentiated liposarcoma (DDLS) with rhabdomyoblastic differentiation and MDM2 amplification. The surgical margins were negative, and the patient had a metastatic workup that included magnetic resonance imaging (MRI) of the abdomen and pelvis. Because of the disease's rarity, there is no clear agreement on radiotherapy and chemotherapy roles.
Keywords: nádory mužských pohlavních orgánů; senioři nad 80 let; Testicular Neoplasms; orchiektomie; Orchiectomy; Humans; Aged, 80 and over; Liposarcoma; Male; Rhabdomyoblasts; liposarkom; testikulární nádory; mužské pohlaví; Genital Neoplasms, Male; lidé; Dedifferentiated; Paratesticular